Asuhan Keperawatan Pada Ny. P dengan Gangguan Sistem Imunologi : Post Operasi Ekstirpasi Tumor Colli Hari Pertama di Ruang Multazam RS PKU Muhammadiyah Surakarta - Ekawati, Rita, Dian Hudiyawati, S.Kep., Ns., M.Kep (2013)
Background: Tumor colli or branchial cyst is a congenital disorder which caused by imperfections obliteration of apartus branchial so remain of cells that will provoke the formation of cysts. In 2013 the incidence of head and neck tumors in PKU Muhammadiyah of Surakarta Hospital until 30 incidence tumor colli. The lack of public knowledge about the disease is also used effects the increase in the incidence of tumors colli because they can not realize early on tumor colli disease and they don't know if the tumor colli left will cause respiratory disorders and indigestion. Objective: To determine nursing care of patients with tumors colli include assessment, intervention, implementation and evaluation of nursing. Result: after 2 days of action for nursing diagnoses that appear three are: pain, there is lack of sleep and there is no infection. In most implementations are compliant with the plan of action that has been applied. Conclusion: after action for nursing care during 3 x 24 hours began April 30th 2013 until May 1th 2013 for Ny. P with post operation tumor colli, cooperation between the health care team and patient or family is indispensable for the success of nursing care to patients. Process nursing care action of patients began from choice diagnoses of nursing, planning, actions, evalutions and documentations.